Patrones de personalidad asociados al comportamiento de consumo de alcohol en la ciudad de Cusco - Acetuna Ccolque, Yency (2018)
Abstract The present investigation relates the personality with the alcohol consumption, following a correlational cross-sectional design, the population is constituted by patients attended in the health establishments of the city of Cusco with a sample of 217 of 16 to 64 years between males and females. women. The objective was to determine the relationship between the variables, using instruments: Inventory of Personality NEO-FFI and Test of Identification of the Disorders Due to the Consumption of Alcohol - AUDIT; the significant level of Cronbach's Alpha (0.612) for NEO-FFI and (0.759) for AUDIT. According to the results, dependence relations between the dimensions of personality neuroticism, extraversion, openness to experience and consciousness are evidenced; On the other hand, there is no dependency relationship between kindness and alcohol consumption. On the other hand, we observe that the neuroticism, extraversion, openness and awareness dimensions are linked to alcohol consumption according to the sociodemographic variables stages of adolescent, young and older adult development; in both sexes and from the rural and urban sectors. In conclusion, there is a relationship between personality dimensions, neuroticism, openness to experience, awareness and alcohol consumption, and some significant relationships according to sociodemographic variables.